State-Corporate Environmental Cover-Up: The Response to the 2010 Gulf of Mexico Oil Spill. (1st October 2014) - Elizabeth A. Bradshaw
Abstract : Developing the concept of state-corporate environmental crime, this article examines the government and corporate response to the 2010 Gulf of Mexico oil spill. US federal responders functioned in coordination with BP and an extensive array of privately contracted oil spill response organizations to systematically conceal the environmental damage caused by the spill through various means. State-corporate responders applied unprecedented amounts of toxic chemical dispersants in an effort to hide the oil, blocked public and media access to response operations, and relied upon a network of federal, state and local law enforcement agencies alongside private security firms to enforce the ban. In combination, these efforts constitute a state-corporate cover-up of environmental crimes in the Gulf of Mexico oil spill.